Analisis Wacana Kritis Pemberitaan Kasus Suap Soemarmo RAPBD 2012 Kota Semarang di Surat Kabar Harian Suara Merdeka - Darmawan, Ratna Riadhini (Jurnal The Messenger, 2014)
This research aim to understand the text, the discourse practice, and the sociocultural practice which Suara Merdeka showed in their publications about bribery case of Semarang s RAPBD 2012 which claims Soemarmo.The theoritical of this study required critical paradigm. Stuart Hall in Eriyanto (2008) wrote that mass media is not produce a news, but they determine reality through words.The research method used critical discourse analysis by Norman Fairclough. Three steps analysis by Faircough are text analysis, discourse practice analysis, and sociocultural analysis. The texts have been analyzed by linguistic, grammar and vocabulary. Discourse practice analysis related to production and consumtion process. Sociocultural analysis related to outside elements of the texts. The researcher collected data by text analyzed and interviewed a journalist and the editor in chief of Suara Merdeka. The study has been done in Semarang.This research found that Suara Merdeka wrote the text about this case very carefully. There was a special agenda setting to write about it. The socioculture practice analysis showed that the capitalist has intervented the editorial.